Citra Tubuh Ideal Perempuan dalam Iklan Televisi - Lida Imelda Cholidah (Anida (Aktualisasi Nuansa Ilmu Dakwah), 2015)
Advertising is one way to convey a message to the target audience are considered, and is used as a means of communication between producers and consumers. As communication tools, ads may expose the description of a product of each goals and objectives. Has an important role in an ad, either in print or electronic media. The use of women in advertising adds to the appeal to enjoy the advertising message. Because women are always displayed visually appealing, even though not necessarily the case. With the visualization of this it tends to cause a variety of different perception of the female image.Female ideal body imaging interpreted as a slim body, with no excess fat proportional portray the image of a beautiful woman. The image formed by the mass media often presents the symbols that represents the ideal female body as a symbol of beauty. Nevertheless imaging and acceptance and rejection of the ideal body will continue to rotate with the growth of industry, politics, advances in medicine, changes in the economy and the media.